Molecular descriptions of functionalised multi layered diamond like/ amorphous carbon coatings. (June 2019) - Awaja, Firas; Wong, Tsz-Ting; Putzer, David; Thaler, Martin; al Taee, Abdulmalik; O'Brien, Timothy
Highlights: A Multi-layer coatings with different functionalities were obtained by plasma deposition of DLC and amorphous carbon films. We developed a correlation, based on ToF-SIMS information, between a plasma deposited DLC/amorphous carbon uniformity, thickness, chemical composition, molecular structure, organics and inorganics contaminants with the plasma deposition conditions. Groups of samples can be identified based on the PCA analyses to explain the thin films associated chemistries at different sputtering conditions. Abstract: Diamond-like carbon (DLC) coatings are increasingly used in multiple applications due to excellent biocompatibility and outstanding mechanical, optical, and electrical properties. However, many aspects of the synthesise and functionality of these films, especially at the surface, are still uncertain. Here, we were successful in synthesising a multi functionality multi-layer DLC and amorphous carbon(a-C:H) coatings, deposited on Si wafers, to create different materials attributes. Time-of-Flight Secondary Ions Mass Spectroscopy (ToF-SIMS), combined with Principal component analysis (PCA) analysis, was used to provide molecular characterisation of the coatings that were synthesized using plasma immersion ions implantation and deposition (PIII&D) technique. We used acetylene (C2 H2 ), methane (CH4 ) and oxygen (O2 ) and their mixtures as precursor in the plasma treatment process. The organic layer (s) deposition's uniformity, thickness, chemical composition, molecular structure, organics and inorganics contaminants in the film were revealed and linked to the plasma deposition conditions. The thickness of the deposited films can be determined according to their Si and O2 content. Samples with higher O content also have higher SiO and NOx contents. ToF-SIMS is successful as a stand-alone technique to provide information and knowledge regarding the surface compositions and the depth interface profile of plasma deposited DLC and a-C:H coatings.